Indigenous, traditional, and folk sports
1 online resource (x, 286 pages)
Keywords: This is the first book to focus on indigenous, traditional, and folk sports and sporting cultures. It examines the significance of sporting cultures that have survived the emergence and diffusion of western sports and have carved out a unique position not only in spite of modernity but also in response to it. Presenting case studies from around the world, including from Europe, Asia, Africa, and the Americas, this book draws on multidisciplinary work from sociology, anthropology, history, cultural studies, and political science, exploring key themes in the social sciences including nationalism, identity, decolonisation, and gender. From Turkish oil wrestling, kabaddi in South Asia, Iroquois lacrosse, to wushu and sumo in East Asia and various European traditional sports, these sporting practices continue to capture the indigenous imagination on the margins of the western hegemonic sport complex. Situated in the fissures between the local, the national, and the global; between the archaic and the modern; and between ritual and record, they inhabit a liminal space of transformation as they assume new cultural and political meanings, offering important perspectives on the complexities and contradictions of modernity. The volume⁰́₉s decolonial perspective lies in its promotion of indigenous and subaltern worldviews through their traditional movement cultures on the margins of the western hegemonic sport complex. This is a fascinating reading for anybody with an interest in sport, nationalism, Indigenous studies, heritage and folklore studies, anthropology, social and cultural history, or globalisation.